2015
DOI: 10.1016/j.lungcan.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and survival of patients with EGFR -mutated non-small cell lung cancer and leptomeningeal metastasis: A retrospective cohort analysis

Abstract: Although median survival after LM-diagnosis in EGFR-mutated NSCLC-patients was poor, a substantial part of the patients had a prolonged survival of more than 6 months. PS of 0-1 at time of diagnosis of LM was associated with prolonged survival. No other patient- or treatment-related characteristics were identified. Further research is warranted to identify treatment strategies that improve survival in EGFR+ NSCLC-patients with LM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 37 publications
(56 reference statements)
5
75
2
Order By: Relevance
“…For afatinib, the cerebral response rate was 35% and the cerebral disease control rate was 66% in patients with CNS disease [7]. There have been a few reports of patients with leptomeningeal carcinomatosis who were treated with EGFR-TKIs, and these have demonstrated that some of the patients achieved prolonged survival [7,8,9,10,11,12,13,14,15,16,17]. …”
Section: Discussionmentioning
confidence: 99%
“…For afatinib, the cerebral response rate was 35% and the cerebral disease control rate was 66% in patients with CNS disease [7]. There have been a few reports of patients with leptomeningeal carcinomatosis who were treated with EGFR-TKIs, and these have demonstrated that some of the patients achieved prolonged survival [7,8,9,10,11,12,13,14,15,16,17]. …”
Section: Discussionmentioning
confidence: 99%
“…A response to therapy and a prolonged overall survival is observed especially in patients with breast cancer (median survival 7-12 months) [31,32], whereas patients with melanoma [33] or lung cancer (irrespective of EGFR mutation [34][35][36]) have a short median survival of approximately 4 months. Nevertheless, even for the latter an extended overall survival (> 12 months) with therapy is possible in individual cases.…”
Section: Prognosismentioning
confidence: 99%
“…About 9% to 10% of patients with NSCLC with EGFRactivating mutations will develop LM either at initial diagnosis or during TKI treatment (9,10). LM is often associated with poor prognosis and represents a terminal event of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…LM is often associated with poor prognosis and represents a terminal event of NSCLC. The median overall survival (OS) after LM diagnosis is 3.1 to 11 months, with $60% death due to LM or LM together with systemic lesions (9)(10)(11)(12)(13). So far, there is no effective treatment, though preliminary clinical activities of osimertinib and AZD3759 in patients with NSCLC with LM have been reported (14,15), and other CNSpenetrant TKIs such as tesevatinib are being developed.…”
Section: Introductionmentioning
confidence: 99%